The high temperature conductivity of magnetite ore as the possible basis for predicting the mineral composition and the genetic peculiarities of the deposits - V. V. Bakhterev (Известия высших учебных заведений: Геология и разведка)
The rock samples from different structural-material complexes of some ultramafic massifs of the Urals have been investigated. The experiments have allowed establishinga dependence of electrical resistance on temperature in the range of 20-800 °C. The electrical parameters lgRo, Eoof studied samples have been defined. There was an inverse linear dependence between the parameters. It is expressed by the formula lgRo = a - bEo. The coefficient a stays practically the same for all studied massifs and plots them (6,2-7,2); the coefficient b - changes continuously from 5,8 to 13,2; its value differs not only for each ultramafic massif, but even for an individual plot within the same massif. Position of the samples on the line lgR = a - bEo with specific coefficients a and b depends on the degree of metamorphism.